ANALISIS TOTAL PRODUCTIVE MAINTANCE (TPM) MENGGUNAKAN METODE OEE DAN FMEA PADA MESIN PRODUKSI PUPUK DOLOMIT PLAN-2 DI PT. XYZ - Dias Afiansyah; Efta Dhardikasari Priyana; Hidayat Hidayat (G-Tech: Jurnal Teknologi Terapan, 2025)
There are several aspects that affect the company's top priority, namely the smooth production process, one of which is machine performance. At PT XYZ during the period January - June 2024 had high downtime caused by ineffective maintenance management, resulting in disruption of production flow and reducing overall productivity. The purpose of this study is to determine the value of machine effectiveness using the OEE method and determine the factors that cause obstruction of the production process. From the calculation results, the average OEE value was 47.70%, below the world-class standard of 85%. In addition, this study identified six major losses with the highest value being equipment failure losses with an average of 48.38%, FMEA analysis showed the highest RPN value of 441 on the machine factor with the failure mode occurring, namely the presence of foreign objects in the raw material entering the crusher machine can cause significant damage to machine components. To increase the effectiveness of production machines at PT. XYZ, corrective actions are needed in machine maintenance and labor vigilance.